Systemic Embolization and Myocardial Infarction due to Clinically Unrecognized Left Atrial Myxoma - Britta Vogel; Dierk Thomas; Derliz Mereles; Wolfgang Rottbauer; Hugo A. Katus (Case Reports in Medicine)
Myxomas are the most common primary tumors of the heart. We report an extraordinary severe case of left atrial myxoma, presenting with stroke, myocardial infarction, and multiple arterial embolism including aorta, splenic and renal arteries, and several peripheral arteries. The patient had previously been diagnosed with systemic vasculitis, a typical but less common finding caused by multiple emboli mimicking vasculitis. The myxoma was removed and atrial septum reconstruction was performed. In summary, early diagnostic differentiation of myxoma from vasculitis is critical, and immediate surgical removal of myxoma is required as the probability of thromboembolic complications increases over time.